2003
DOI: 10.1002/eji.200323765
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus (EBV)‐positive lymphoproliferations in post‐transplant patients show immunoglobulin V gene mutation patterns suggesting interference of EBV with normal B cell differentiation processes

Abstract: In a model for persistent infection, Epstein-Barr virus (EBV) uses the germinal center (GC) reaction to establish persistence in memory B cells. To study whether EBV adopts to normal B cell differentiation processes also in EBV-associated lymphoproliferative diseases, we micromanipulated EBV + cells from biopsies of five patients with post-transplantation lymphoproliferative disease (PTLD) and one unusual Hodgkin lymphoma with many small EBV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
47
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 37 publications
8
47
0
1
Order By: Relevance
“…19 Interest in viral infection of GC cells was reawakened by the observation that EBV-positive PTLD tumors, many of which had full latent antigen expression, often arise from B cells with atypical, even nonfunctional, IgH alleles. [8][9][10] The present work provides strong evidence that EBV infection in vitro can indeed rescue the failed products of GC reactions, leading to the outgrowth of surface immunoglobulin-negative LCLs with functionally inactivated IgH alleles; we recently learned of similar findings in 2 other laboratories. 20,21 Such activity likely reflects not just the well-documented growth-transforming function of EBV but also the ability of certain EBV latent proteins to protect B cells from apoptosis.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…19 Interest in viral infection of GC cells was reawakened by the observation that EBV-positive PTLD tumors, many of which had full latent antigen expression, often arise from B cells with atypical, even nonfunctional, IgH alleles. [8][9][10] The present work provides strong evidence that EBV infection in vitro can indeed rescue the failed products of GC reactions, leading to the outgrowth of surface immunoglobulin-negative LCLs with functionally inactivated IgH alleles; we recently learned of similar findings in 2 other laboratories. 20,21 Such activity likely reflects not just the well-documented growth-transforming function of EBV but also the ability of certain EBV latent proteins to protect B cells from apoptosis.…”
Section: Resultssupporting
confidence: 65%
“…[5][6][7] Recent studies have found that most PTLD tumors carry hypermutated immunoglobulin sequences, many of which are atypical of conventional antigenselected memory cells. [8][9][10] Indeed, some tumors lacked surface immunoglobulin and had functionally inactivated immunoglobulin sequences, 8 highlighting parallels with another EBV-associated B-cell malignancy, Hodgkin lymphoma (HL), in which the tumor cells are again surface immunoglobulin negative and often carry similarly "crippled" immunoglobulin genes. 11 These findings suggest that EBV infection can promote the survival of atypical post-germinal center (GC) B cells carrying unfavorable or even inactivating immunoglobulin gene mutations.…”
Section: Introductionmentioning
confidence: 99%
“…52 Also, EBV infection is found in many post-transplant lymphoproliferative disorders with crippled IGV genes. 24,50,51 Overall, these observations support a central role of EBV in the pathogenesis of lymphomas with impaired B-cell receptor.…”
Section: Discussionsupporting
confidence: 58%
“…These features are at variance with those observed in other lymphomas associated with immunodeficiency, namely post-transplant lymphoproliferative disorders, whose molecular features suggest a minor role for antigen stimulation. 24,50,51 In particular, the different role exerted by B-cell receptor stimulation in the pathogenesis of HIV-NHL and posttransplant lymphoproliferative disorders is indicated by the presence of IGV inactivation by crippling mutations introduced by somatic hypermutation in nearly a quarter of post-transplant lymphoproliferative disorders, 24,50,51 whereas crippling mutations of IGV rearrangements are a very rare finding among HIV-NHL (3%; this study). Interestingly, each case of HIV-NHL carrying IGV inactivation by crippling mutations was positive for EBV infection of the tumor clone.…”
Section: Discussionmentioning
confidence: 67%
“…Among more than 50 cases of classical HL, 11 of 12 cases in which such crippling mutations have been identified were EBVinfected, while 19 of 43 cases lacking evidence for crippling muta- Cases without crippling mutations 19 24 This overview is based on data from refs. 3,4,6,11,62,63,65,66,68,[90][91][92][93][94]. Not included is an EBV-negative case in which only a subclone of the HRS cells is crippled (case 3), 92 and 1 case lacking crippling mutations in which a subclone of the HRS cells is EBVinfected.…”
mentioning
confidence: 99%